Retrospective analysis of oral and maxillofacial biopsies: An institutional study - Gurunathan Ulaganathan; Sitharaju Santhosh Babu; Murugesan Senthilmoorthy; Varun Prasad; Sundarrajan Kalaiselvan; Ramasamy Subramanian Asok Kumar (Wolters Kluwer Medknow Publications, 2020)
Aim: To determine the preponderance and the distribution of pathological lesions in oral and maxillofacial region reported in and around the Madurai city. Study Design: Retrospective study on the oral and maxillofacial biopsies taken during 11 years period from 2007 to 2018 in a CSI Dental College, Madurai, Tamilnadu. A total of 1000 cases were analyzed and 904 were selected. The parameters recorded were age, sex, area, and the histopathological report obtained. Descriptive statistics was used for analysis. Result: The most common soft tissue lesion was traumatic fibroma (16.1%) and the prevalent hard tissue lesion was periapical cyst (12.7%). The more common oral malignant tumour observed was squamous cell carcinoma (7.3%) and benign tumor was ameloblastoma (5.3%). The frequently affected sites were mandible (36.1%) and buccal mucosa (19.8%). There was more predilection among male than females. The frequency of lesion is common in age group of 31-60 years. A considerable similarity was observed between age, type of lesion and its location. Conclusions: This study evaluated chronic periapical lesions were the most common hard tissue lesions and fibromas in soft tissue category. The idea of this histopathological study concludes on the requirement for biopsy to rule out type of the lesion and its severity to start up the earlier management.